Effect of a Teams Games Tournament Using Quizizz on Mathematical Reasoning as Viewed from the Level of Mathematics Anxiety - Tantia Hediyanti Candra; Abd Aziz; Eka Rahayu (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematics instruction in schools still tends to be teacher-centered, so student engagement in developing mathematical reasoning is not yet optimal. This leads to students struggling to provide logical justifications and relying on formulas, as well as being influenced by affective factors such as mathematics anxiety; therefore, innovative instructional models such as the Teams Games Tournament (TGT) supported by Quizizz are needed. This study aims to analyze the effect of the Quizizz-assisted TGT model on students’ mathematical reasoning abilities as viewed from their level of mathematics anxiety regarding sequences and series. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group pretest-posttest design. The research subjects were 11th-grade students at SMA Istiqlal, consisting of 25 students in the experimental class and 26 students in the control class. The instruments used were a mathematical reasoning essay test and a mathematics anxiety questionnaire using a Likert scale, both of which were validated and reliable. Data analysis was performed using an independent samples t-test, one-way ANOVA, and two-way ANOVA. The results showed that the average posttest score for the experimental class (84.36) was higher than that of the control class (76.73), with a significance level of 0.000 < 0.05; there was a difference based on mathematics anxiety with a significance level of 0.032 < 0.05; however, there was no interaction between the two variables with a significance level of 0.549 > 0.05. Thus, TGT assisted by Quizizz is effective in improving mathematical reasoning and can serve as an interactive learning alternative while reducing students’ mathematics anxiety.